Aspirin use and bleeding events during thrombocytopenia after autologous stem-cell transplantation for multiple myeloma - Neuendorff, Nina Rosa; Boshikova, Boryana; Frankenstein, Lutz; Kirchner, Marietta; Rohde, Christian; Goldschmidt, Hartmut; Frey, Norbert; Müller-Tidow, Carsten; Jordan, Karin; Sauer, Sandra; Janssen, Maike (Frontiers in Oncology, 2023)
Background: In patients with cardiovascular comorbidities which necessitate antiplatelet therapy (APT), its optimal management during chemotherapy-induced thrombocytopenia remains elusive, as the risk of bleeding has to be balanced against the risk of cardiovascular events. The purpose of this study was to assess the risk for bleeding with APT during thrombocytopenia in patients with multiple myeloma undergoing high-dose chemotherapy and subsequent autologous stem-cell transplant (ASCT) with and without acetylsalicylic acid (ASA) as comedication. Methods: We assessed patients who underwent ASCT at the Heidelberg University Hospital between 2011 and 2020 for bleeding events, management strategies for ASA intake during thrombocytopenia, transfusion requirements, and the occurrence of cardiovascular events. Results: 57/1113 patients continued ASA until at least one day after ASCT, thus, a continuous platelet inhibition during thrombocytopenia was assumed. Most of the patients (41/57) continued ASA until a platelet count of 20-50/nl. This range reflects the kinetics of thrombocytopenia and non-daily measurements of platelets during ASCT. A tendency towards a higher risk for bleeding events in the ASA group was demonstrated (1.9% (control group) vs. 5.3% (ASA), p=0.082). Risk factors for bleeding in multivariate analysis were duration of thrombocytopenia <50/nl, history of gastrointestinal bleeding, and diarrhea. Factors predicting the duration of thrombocytopenia were age >60 years, hematopoietic stem-cell transplantation comorbidity index ≥3, and an impaired bone marrow reserve at admission. Cardiovascular events occurred in three patients, none of them took ASA or had an indication for APT. Conclusions: Intake of ASA until thrombocytopenia with platelet count 20-50/nl appears safe although an elevated risk cannot be excluded. If ASA is indicated for secondary prevention of cardiovascular events, the evaluation of risk factors for bleeding and prolonged time of thrombocytopenia before conditioning is crucial to adapt the strategy for ASA intake during thrombocytopenia.